Protecting personnel at hazardous waste sites - Martin, William F.; Gochfeld, Michael (Butterworth-Heinemann, 2000)
The latest edition of this book brings together a wide range of occupational safety and health recommendations and practices directly applying to hazardous waste site cleanups. In addition to providing the most current information on maximum protection for cleanup personnel, this book is a practical, authoritative guide for those involved in cleanup operations. The completely updated third edition cites the newest OSHA and NIOSH recommendations that have developed over the past decade and explores the new federal emphasis in hazardous waste site cleanups such as radiation safety, toxicology, unexploded ordnance, OSHA training, EPA training, and site health and safety plans. Covers a wide array of occupational safety and health practices and recommendations applicable to hazardous waste clean-up Provides the most up-to-date information on maximum protection for workers Cites the newest OSHA and NIOSH recommendations and explores federal government emphases in the area.